The Structural Marginalization of Artisanal Fishing Communities: The Case of La Boquita - Doyon, Sabrina (Anthropologica, 2022)
The fishing community of La Boquita located on the West coast of Mexico provides a case study of the structural marginalization that faces artisanal fishing communities. Employing political ecology theory, this article analyzes (1) the conflicts between the community and the government regarding their property rights over the territory, (2) environmental degradation induced by tourism development, and (3) the pressures the sport fishing industry places on artisanal fishing practices. The article analyzes how these changes influence the community's socio-economic organization and jeopardize La Boquita's social reproduction.